2015
DOI: 10.1080/15548627.2015.1034402
|View full text |Cite
|
Sign up to set email alerts
|

The GST-BHMT assay reveals a distinct mechanism underlying proteasome inhibition-induced macroautophagy in mammalian cells

Abstract: #These authors equally contributed to this work.Keywords: BHMT, cargo receptors SQSTM1/p62 and NBR1, MTOR, PRKAA/AMPK, proteasome inhibition, selective macroautophagyAbbreviations: ACACA/B, acetyl-CoA carboxylase a/b; ACTB, actin, b; ATF4, activating transcription factor 4; ATF6, activating transcription factor 6; ATG7, autophagy-related 7; Baf A1, bafilomycin A 1 ; BCL2, B-cell CLL/lymphoma 2; BECN1, Beclin 1, autophagy-related; BHMT, betaine-homocysteine S-methyltransferase; CTNNB1, catenin (cadherin-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Xia et al (25) have revealed that high expression of P4HB in liver cancer tissues was associated with poor survival. However, there is also evidence suggesting that the low expression of P4HB could lead to proteasome inhibition-induced autophagy (78), since the boundary between apoptosis and autophagy has always been controversial due to tumor heterogeneity (79). Based on the present results revealing that the patients with hypermethylation and low expression of P4HB had poor prognosis, it was hypothesized that hypermethylation of P4HB in prostate cancer would activate autophagy of prostate cancer cells and promote the tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al (25) have revealed that high expression of P4HB in liver cancer tissues was associated with poor survival. However, there is also evidence suggesting that the low expression of P4HB could lead to proteasome inhibition-induced autophagy (78), since the boundary between apoptosis and autophagy has always been controversial due to tumor heterogeneity (79). Based on the present results revealing that the patients with hypermethylation and low expression of P4HB had poor prognosis, it was hypothesized that hypermethylation of P4HB in prostate cancer would activate autophagy of prostate cancer cells and promote the tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, treatment with MG132 or bortezomib in human colon cancer cells produced ER-stress and UPR dependent autophagy activation. Autophagy was abolished by IRE1α knockdown, or by treatment with the JNK inhibitor SP600125 (Ding et al, 2007), but was independent of XBP-1 signaling (Ding et al, 2007;Rui et al, 2015). Finally, proteasome inhibition with bortezomib in human prostate cancer cells, and immortalized mouse embryonic fibroblasts promoted autophagy activation and upregulated expression of ATG5 and ATG7, which depended on phosphorylation of eIF2α, a downstream element of the PERK arm of the UPR (Zhu et al, 2010).…”
Section: Pharmacological Approachesmentioning
confidence: 95%
“…However, Rui et al provided inconsistent data that under nutrient-rich conditions, inactivation of proteasome function induced an autophagy-dependent process and relied on the critical autophagy components ATG7 and ULK1, but is not involved the upstream autophagy regulators MTORC1 or AMPK. Further, the authors demonstrated that it otherwise depends on ER stress pathway (20).…”
Section: Introductionmentioning
confidence: 97%